Examination of Research Conducted on the Use of Artificial Intelligence in Science Education - Faruk Arıcı (Sakarya University Journal of Education)
The advancement of artificial intelligence (AI) has been significantly driven by developments in machine learning and neural networks. As AI becomes increasingly pervasive, its applications are diversifying, with notable penetration in sectors such as health, education, social media, robotics, and entertainment. One area in which AI is being deployed is science education. The objective of this study is to examine the research that incorporates AI within the field of science education. By analysing trends in the reviewed studies, this research identifies the countries, institutions, journals and scholars that are the most prominent contributors to this field of enquiry. The findings suggest that the incorporation of artificial intelligence into science education is still in its infancy, with a paucity of widespread implementation. However, there is a discernible increase in the quantity of published works, with an emerging emphasis on the assessment of learning outcomes and the enhancement of academic performance. The findings indicate that the United States is the leading country in terms of publications related to AI in science education, accounting for 38% of the total contributions. Additionally, Türkiye has emerged as a notable contributor in this field, demonstrating a growing presence. The Journal of Science Education and Technology was identified as the preeminent journal publishing research on AI. Furthermore, the findings revealed that GPT was the most frequently utilised tool in this context. In light of these findings, it is recommended that future investigations into the application of artificial intelligence (AI) in science education employ a range of AI tools and explore the development of higher-order thinking skills.